A microRNA-4516 inhibitor sensitizes chemo-resistant gastric cancer cells to chemotherapy by upregulating ING4. Issue 66 (12th November 2018) - Liu, Jun-bao; Chen, Dan; Liu, Hai-xia; Sha, Huan-huan; Song, Dan; Bao, Ting-ting; Lu, Jian-wei; Yu, Chen
Abstract : MicroRNA (miRNA) is an important factor in the regulation of gene transcription. Abstract : Objective MicroRNA (miRNA) is an important factor in the regulation of gene transcription. This study was aimed at investigating the role of miR-4516 in the chemoresistance of gastric cancer cells. Methods miR-4516 expression levels were measured in gastric cancer cell line SGC7901 and in 5-fluorouracil (5-FU)-resistant SGC7901 cells (SGC7901/5-FU) via microarray analysis and RT-PCR. A miR-4516 inhibitor and negative controls were transfected into SGC7901/5-FU cells. A miR-4516 mimic and negative controls were transfected into SGC7901 cells. CCK8 and flow-cytometric assays were performed to evaluate the sensitivity of SGC7901/5-FU cells to 5-FU. Western blot experiments detected the expression of Bcl-2, Bax, Caspase-3, P-gp and ING4 protein. Results Additionally, ING4 was demonstrated to be downregulated in SGC7901/5-FU cells and inversely correlated with miR-4516 expression. Rescue experiments revealed that overexpression of ING4 attenuated the inhibitory effects of miR-4516 on the proliferation of gastric cancer cells. ING4 was predicted to be a potential target of miR-4516. Synergism of the inhibitory effects correlated with a reduction in the expression of the anti-apoptotic protein Bcl-2 and the drug resistance-related protein P-gp as well as strong expression of apoptosis-related proteins (Bax, Caspase-3). Thus, a miR-4516 inhibitor sensitized gastric cancer SGC7901/5-FU cells to 5-FU by enhancing apoptosis. We then corroborated these results with in vivo experiments. Conclusion We found that miR-4516 might be a potential therapeutic target in chemo-resistant gastric cancer.